Maxillary canine - First premolar transposition: Restoring normal tooth order with segmented mechanics - Capelozza Filho, Leopoldino [UNESP]; Cardoso, Mauricio de Almeida [UNESP]; Tien, Li An [UNESP]; Bertoz, Francisco Antonio [UNESP] (The Angle Orthodontist (EH Angle Education & Research Foundation), 2007)
Tooth transpositions present at a relatively low incidence in the world population and primarily affect maxillary canines and premolars. Treatment of this disturbance should take into account aspects such as facial pattern, age, malocclusion, tooth-size discrepancy, stage of eruption, and magnitude of the transposition. Mechanics for correction should be entirely individualized, reducing the risks and adverse effects. Practitioners often select simpler options, indicating extraction of permanent teeth, which is an irreversible procedure that may bring about damages to the patient. This study presents a case report and treatment of unilateral transposition of maxillary canine and premolar with repositioning of affected teeth to their respective normal positions. © 2006 by The EH Angle Education and Research Foundation, Inc.
Keywords: Corrective orthodontics; Segmented mechanics; Transposition; canine tooth; case report; child; female; human; maxilla; methodology; orthodontics; pathology; premolar tooth; tooth disease; Bicuspid; Child; Cuspid; Female; Humans; Maxilla; Orthodontics, Corrective; Tooth Eruption, Ectopic